2018
DOI: 10.1155/2018/9017828
|View full text |Cite
|
Sign up to set email alerts
|

The In Vitro Antioxidant Activity and Inhibition of Intracellular Reactive Oxygen Species of Sweet Potato Leaf Polyphenols

Abstract: The in vitro antioxidant activity and inhibition of intracellular reactive oxygen species (ROS) of the total and individual phenolic compounds from Yuzi No. 7 sweet potato leaves were investigated in this study. Sweet potato leaf polyphenols possessed significantly higher antioxidant activity than ascorbic acid, tea polyphenols, and grape seed polyphenols. Among the individual phenolic compounds, caffeic acid showed the highest antioxidant activity, followed by monocaffeoylquinic acids and dicaffeoylquinic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…1 leaves (2109 ± 0.15 mg/100 g DW), and Shangshu 19 leaves (1855 ± 0.17 mg/100 g DW), with significant differences among them (Table 2, P < 0.05). Our findings were in agreement with those reported by Lu et al 25 and Sun et al 12 in SPL. Our results also showed differences in phenolic acid composition which might be attributed to the differences between cultivars, the state of maturity, genotype, and environmental conditions, resulting in different phenolic acid constituents (ie, mono-, di-, and tri-caffeoylquinic acids).…”
Section: Individual Phenolic Compositionsupporting
confidence: 94%
See 1 more Smart Citation
“…1 leaves (2109 ± 0.15 mg/100 g DW), and Shangshu 19 leaves (1855 ± 0.17 mg/100 g DW), with significant differences among them (Table 2, P < 0.05). Our findings were in agreement with those reported by Lu et al 25 and Sun et al 12 in SPL. Our results also showed differences in phenolic acid composition which might be attributed to the differences between cultivars, the state of maturity, genotype, and environmental conditions, resulting in different phenolic acid constituents (ie, mono-, di-, and tri-caffeoylquinic acids).…”
Section: Individual Phenolic Compositionsupporting
confidence: 94%
“…7 These variations are ascribed to differences in color, variety, and environmental and processing conditions. 12 Bioactive components described in sweet potato comprise phenolic acids, such as caffeic acid and caffeoylquinic acid derivatives, including mono-, di-and tri-caffeoylquinic acids 13 ; flavonoids, such as astragalin, quercetin, kaempferol, and myricitrin 14 ; and cyanidin or peonidin-type anthocyanins. 9,15 Zengin et al 16 investigated TPC in SPL and found a range of 73.10 ± 3.75 to 89.26 ± 1.34 gallic acid equivalents (GAE) mg/g extract.…”
mentioning
confidence: 99%
“…Previously, it has been shown that the presence of these compounds could help in mitigating aflatoxin contamination in groundnut [ 55 ]. Likewise, genetic manipulation of crops to improve the flavonoids/anthocyanin/polyphenols content has been broadly used to enhance the antioxidant content and reduce susceptibility to diseases (biotic stress) including fungal diseases [ 56 , 57 , 58 , 59 ]. Furthermore, application of flavonoids/polyphenol can significantly reduce the growth of A. flavus and toxin production [ 55 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the current research study did not focus on the mechanisms whereby which the nutritional, chemical, antioxidant and bioactive compounds within the GLVs were able to mitigate the risks for CVD, several metabolic pathways may be initiated or suppressed that may to some extent offer insight to the observed findings. For example, reductions in oxidative stress, inflammation, blood pressure and improved endothelial function may be mediated by compounds such as nitrates [ 82 ], phytochemicals [ 83 ], flavonoids [ 84 ], polyphenols [ 85 ] and omega-3 fatty acids [ 86 ], which are commonly found in GLVs such as collard greens, purslane and sweet potato greens. While brown and white adipose tissue levels were not measured, research has demonstrated that these tissues play a vital role in lipid storage, endocrine function, adipokine concentrations and inflammation [ 87 ].…”
Section: Discussionmentioning
confidence: 99%